Enhancing the Capacity of Musholla Management in Organizing Social and Religious Activities During the Month of Ramadan - Agrasadya; Santi Octavianti; Dewi Lestari (Simfoni Ilmu Cindekia, 2025)
Ramadan serves as a pivotal moment for Muslim communities to engage in both worship and social solidarity. Mushollas, as local prayer and community centers, play a crucial role in facilitating religious gatherings, charity distributions, communal iftar events, and other social initiatives. However, many musholla administrators often encounter difficulties in planning, organizing, and evaluating such activities effectively due to limited managerial skills and lack of structured guidance. This community service program aimed to enhance the capacity of musholla administrators by providing training in program planning, volunteer management, logistics coordination, and post-activity evaluation. The method consisted of interactive workshops, coaching sessions, and practical simulations conducted over five days at Musholla Al-Muqorrobin in Pamulang, South Tangerang. Results showed a notable improvement in the ability of the management team to organize and implement Ramadan programs in a more structured, transparent, and impactful manner. The program also fostered stronger coordination among volunteers and increased community participation. This initiative demonstrates that targeted managerial capacity-building programs can significantly strengthen the social and religious functions of local religious institutions.